Nuclear Transport Deficits in Tau-Related Neurodegenerative Diseases - Diez, Lisa; Wegmann, Susanne (Frontiers in Neurology, 2020)
Tau is a cytosolic microtubule binding protein that is highly abundant in the axons of the central nervous system. However, alternative functions of tau also in other cellular compartments are suggested, for example, in the nucleus, where interactions of tau with specific nuclear entities such as DNA, the nucleolus, and the nuclear envelope have been reported. We would like to review the current knowledge about tau–nucleus interactions and lay out possible neurotoxic mechanisms that are based on the (pathological) interactions of tau with the nucleus.